2018
DOI: 10.1016/j.watres.2017.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Impacts from urban water systems on receiving waters – How to account for severe wet-weather events in LCA?

Abstract: Sewage systems are a vital part of the urban infrastructure in most cities. They provide drainage, which protects public health, prevents the flooding of property and protects the water environment around urban areas. On some occasions sewers will overflow into the water environment during heavy rain potentially causing unacceptable impacts from releases of untreated sewage into the environment. In typical Life Cycle Assessment (LCA) studies of urban wastewater systems (UWS), average dry-weather conditions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…It can be seen that, the selection of appropriate functional unit is prominent as the total treated water discharge volume to the environment is more in the wet season than the dry season, leading to the possible higher total pollutant mass load to the environment. It is noteworthy that although FU1 has been widely used for seasonal LCA assessment of WWTP Lorenzo-Toja et al 2016;Li et al 2017;Risch et al 2018), effects from the variation of influent compositions and flow could not be reflected very well if only using per unit volume as a functional unit (Rodriguez-Garcia et al 2011;Piao et al 2016). The functional unit as per kgPO 4 3 -eq removed based on eutrophying substances removal (e.g.…”
Section: Environmental Impact Of Two Wwtps In Wet and Dry Seasons Usimentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen that, the selection of appropriate functional unit is prominent as the total treated water discharge volume to the environment is more in the wet season than the dry season, leading to the possible higher total pollutant mass load to the environment. It is noteworthy that although FU1 has been widely used for seasonal LCA assessment of WWTP Lorenzo-Toja et al 2016;Li et al 2017;Risch et al 2018), effects from the variation of influent compositions and flow could not be reflected very well if only using per unit volume as a functional unit (Rodriguez-Garcia et al 2011;Piao et al 2016). The functional unit as per kgPO 4 3 -eq removed based on eutrophying substances removal (e.g.…”
Section: Environmental Impact Of Two Wwtps In Wet and Dry Seasons Usimentioning
confidence: 99%
“…Since 1990s, LCA has been applied to the field of wastewater treatment (Corominas et al 2013). In a study with LCA, Risch et al (2018) reported that loads from storm events contributed significantly to eutrophication and ecotoxicity of WWTPs in Responsible editor: Philippe Loubet Electronic supplementary material The online version of this article (https://doi.org/10.1007/s11356-020-08038-2) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of rain events, untreated wastewater and stormwater may be discharged via sewer overflows to creeks and lakes, when the hydraulic capacity of either wastewater treatment plant or of sewer system locally is exceeded. These discharge events can negatively impact natural aquatic environments since organic pollutant concentrations may exceed environmental quality standards (Launay et al 2016;Mutzner et al 2016;Risch et al 2018;Brudler et al 2019). In stormwater, the occurrence of polar organic pollutants (pharmaceuticals, pesticides subsequent referred to as contaminants) depends strongly on local factors, including land use, substance application, rain fall intensity and duration, as well as dry periods between storms.…”
Section: Introductionmentioning
confidence: 99%
“…The growing demand for resources and services has increased the pressure for agricultural and industrial activities, and urban development (Neumann et al 2015;van Vliet et al 2015). Estuaries have become highly vulnerable to this pressure, due to the continuous input of municipal, agricultural and industrial runoff, storm water discharges and accidental wastewater overflows (de los Ríos et al 2016;Risch et al 2018;Rodrigues et al 2017;Willis et al 2017). These stressors, added to the increase in sedimentation have made estuaries a sink for pollutants with affinity for small particles (Reichelt-Brushett et al 2017;Swales et al 2012;Vermeiren et al 2016).…”
Section: Introductionmentioning
confidence: 99%